Inhibition of vacuolar ATPase attenuates the TRAIL-induced activation of caspase-8 and modulates the trafficking of TRAIL receptosomes - Horova, Vladimira; Hradilova, Nada; Jelinkova, Iva; Koc, Michal; Svadlenka, Jan; Brazina, Jan; Klima, Martin; Slavik, Josef; Hyrslova Vaculova, Alena; Andera, Ladislav (The FEBS journal, 2013)
Tumour necrosis factor (TNF) related apoptosis inducing ligand (TRAIL), a membrane-bound ligand from the TNF family, has attracted significant attention due to its rather specific and effective ability to induce apoptotic death in various types of cancer cells via binding to and activating its pro-apoptotic death receptors. However, a significant number of primary cancer cells often develop resistance to TRAIL treatment, and the signalling platform behind this phenomenon is not fully understood. Upon blocking endosomal acidification by the vacuolar ATPase (V-ATPase) inhibitors bafilomycin A1 (BafA1) or concanamycin A, we observed a significantly reduced initial sensitivity of several, mainly colorectal, tumour cell lines to TRAIL-induced apoptosis. In cells pretreated with these inhibitors, the TRAIL-induced processing of caspase-8 and the aggregation and trafficking of the TRAIL receptor complexes were temporarily attenuated. Nuclear factor κB or mitogen activated protein/stress kinase signalling from the activated TRAIL receptors remained unchanged, and neither possible lysosomal permeabilization nor acid sphingomyelinase was involved in this process. The cell surface expression of TRAIL receptors and their TRAIL-induced internalization were not affected by V-ATPase inhibitors. The inhibitory effect of BafA1, however, was blunted by knockdown of the caspase-8 inhibitor cFLIP. Altogether, the data obtained provide the first evidence that endosomal acidification could represent an important regulatory node in the proximal part of TRAIL-induced pro-apoptotic signalling.
Keywords: Sphingomyelin Phosphodiesterase; signální transdukce; Signal Transduction; transport proteinů; Macrolides; Apoptosis; Humans; endozomy; Endosomes; Sphingolipids; sfingomyelinfosfodiesterasa; FLIP (buněčný); TRAIL receptory; Protein Transport; Down-Regulation; caspase-8; Death Domain Receptor Signaling Adaptor Proteins; Antineoplastic Agents; lidé; acidification; Enzyme Activation; CASP8 and FADD-Like Apoptosis Regulating Protein; apoptosis; down regulace; protein TRAIL; vakuolární protonové ATPasy; apoptóza; signální adaptorové proteiny receptorové domény smrti; TNF-Related Apoptosis-Inducing Ligand; V-ATPase; Caspase 8; Hydrogen-Ion Concentration; TRAIL; sfingolipidy; nádorové buněčné linie; protinádorové látky; kaspasa 8; Receptors, TNF-Related Apoptosis-Inducing Ligand; Cell Line, Tumor; aktivace enzymů; koncentrace vodíkových iontů; Vacuolar Proton-Translocating ATPases; makrolidy